Lycopene Inhibits Urotensin-II-Induced Cardiomyocyte Hypertrophy in Neonatal Rat Cardiomyocytes. (25th May 2014) - Chao, Hung-Hsing; Sung, Li-Chin; Chen, Cheng-Hsien; Liu, Ju-Chi; Chen, Jin-Jer; Cheng, Tzu-Hurng
Abstract : This study investigated how lycopene affected urotensin-II- (U-II-) induced cardiomyocyte hypertrophy and the possible implicated mechanisms. Neonatal rat cardiomyocytes were exposed to U-II (1 nM) either exclusively or following 6 h of lycopene pretreatment (1–10 μ M). The lycopene (3–10 μ M) pretreatment significantly inhibited the U-II-induced cardiomyocyte hypertrophy, decreased the production of U-II-induced reactive oxygen species (ROS), and reduced the level of NAD(P)H oxidase-4 expression. Lycopene further inhibited the U-II-induced phosphorylation of the redox-sensitive extracellular signal-regulated kinases. Moreover, lycopene treatment prevented the increase in the phosphorylation of serine-threonine kinase Akt and glycogen synthase kinase-3beta (GSK-3 β ) caused by U-II without affecting the protein levels of the phosphatase and tensin homolog deleted on chromosome 10 (PTEN). However, lycopene increased the PTEN activity level, suggesting that lycopene prevents ROS-induced PTEN inactivation. These findings imply that lycopene yields antihypertrophic effects that can prevent the activation of the Akt/GSK-3 β hypertrophic pathway by modulating PTEN inactivation through U-II treatment. Thus, the data indicate that lycopene prevented U-II-induced cardiomyocyte hypertrophy through a mechanism involving the inhibition of redox signaling. These findings provide novel data regarding the molecular mechanisms by which lycopene regulates cardiomyocyte hypertrophy.